The Role of Home Bleaching Agent on the Fracture Toughness of Resin Composites Using Four-Point Bending Test - Ghazvini Ferooz M; Azadeh N; Barahman N; Azar MR (Shiraz University of Medical Sciences, 2014)
Statement of Problem: Resin composites are a common type of tooth coloured restorative materials. These materials are brittle and their major shortcomings are sensitivity to flaws and defects, low tensile strength, and susceptibility to catastrophic failure.The role of home bleaching agents on the fracture toughness of resin composites using four-point bending test is scanty. Objectives: To compare the fracture toughness (KIc) of resin composites on a fourpoint bending test and to assess the effect of distilled water and a home bleaching agent on the resistance of the materials to fracture. Materials and Methods: seventy-two bar-shaped specimens were prepared from three materials: Rok (SDI), Estelite (Tokuyama), and Vit-l-escence (Ultradent) and divided into three groups. Two groups were assigned as "control" and conditioned in distilled water at 37oC for 24 hours or 21 days, respectively. The specimens in the third group (treatment) were stored in distilled water for 21 days and bleached using Polanight (SDI) for 2 hours daily. For each material, a total of 24 disc-shaped specimens were prepared and after each time interval loaded in a four-point bending test using a universal testing machine with a crosshead speed of 0.5 mm/m. The maximum load to specimen failure was recorded and the KIc was calculated. Results: Statistical analysis using two-way ANOVA showed a significant relationship between materials and treatment (P<0.05). Tukey's test showed that after 24 hours of immersion in distilled water, KIc was not significantly different between materials; Rok revealed the highest value followed by Estelite and Vit-l-escence. The bleaching agent significantly decreased the KIc values of Estelite and Rok while it did not affect that of Vita-l-escence. Immersion in distilled water for all resin composites caused a significant decrease in KIc. Conclusion: The fracture toughness of the resin composites was affected by the bleaching agent and 21day immersion in distilled water.